Prinsip Kebebasan Hakim dalam Memutus Perkara Sebagai Amanat Konstitusi - Firman Floranta Adonara (Jurnal Konstitusi, 2015)
The principle of judicial independence is part of the judicial power. Judicial power is independent of state power to conduct judiciary to uphold law and justice based on Pancasila and the 1945 Constitution, for the implementation of the legal state of the Republic of Indonesia, as requested Article 24 of the 1945 Constitution principle of judicial independence in carrying out his duties as a judge, it can give you the sense that judges in performing their duties of judicial power should not be bound by any and / or pressured by anyone, but free to do anything. The principle  of judicial independence is an independence or freedom possessed by the judiciary for the creation of a decision that is both objective and impartial. The Indonesian judges understand and implement the meaning of judicial independence as a responsible freedom, freedom in order corridor legislation applicable to the principal duty of the judicial authorities in accordance procedural law and regulations in force without being influenced by the government, interests, pressure groups , print media, electronic media, and influential individuals.